"Cold" Process for IBC c-Si Solar Cells Fabrication. (August 2016) - López, Gema; Ortega, Pablo R.; Martín, Isidro; Voz, Cristóbal; Orpella, Albert; Alcubilla, Ramón
Abstract: In this work we have developed an innovative fabrication process of n-type interdigitated back contact (IBC) c-Silicon solar cells. The main feature is that all the highly-doped regions in the cell have been entirely fabricated through laser processing of dielectric layers, avoiding the high temperature steps typically found in conventional diffusion processes. Additionally, we have reduced the patterning steps. We use an Al2 O3 film deposited by thermal-ALD that passivates the front and rear surfaces acting simultaneously as antireflection coating and aluminium source for p+ emitter formation. Back surface field (BSF) is achieved by the introduction of phosphorous atoms from a N doped a-SiCx stack deposited by PECVD. This stack consists of intrinsic a-SiCx as passivating layer, a-Si (n type) as phosphorous source and a-SiCx carbon rich as protective capping layer. Dielectrics were laser processed in a point- like structure to achieve highly-doped regions. As a proof of concept we have developed four 9 cm 2 -IBC varying the emitter coverage with efficiencies up to 15.5%. However, our 3D simulations suggest that efficiency beyond 20% is reachable by future improvements in the laser process stage.